God knows where I am [videorecording (DVD)] - Wilder, Jedd; Wilder, Jedd; Wilder, Todd; Wilder, Todd; Singer, Lori, 1957- ([publisher not identified], 2018)
The story of Linda Bishop, a homeless woman whose body was found in an abandoned New Hampshire farmhouse, with a diary of her life's journey laying beside her.